Marina Cvetaeva Studien und Materialien - Lampl, Horst; Hansen-Löve, Aage A. (Wiener Slawistischer Almanach - Sonderbaende, 1981)
The purpose of th is study is to describe certain features of Tsvetaeva's intermediate world and to demonstrate its relation to several peculiarities of Tsvetaeva's poetics, specifically, her predilection for oxymoron and the ambiguous nature and behavior of her lyrical personae. Furthermore, these important structural elements are viewed as inherent in Tsvetaeva's dichotomous poetic vision. Two thematic cores, "love" and "poetry", are analyzed with particular attention given to the investigation of the nature of their opposition. An analysis of the "love"/"poetry" pair specifically serves as a vehicle for obtaining information about the intermediate world.